First Analytical Solution of Intracellular life Cycle of SARS-CoV-2 - Isea, Raúl; Mayo-García, Rafael (Journal of Model Based Research, 2022)
The goal of this paper is to show that it is possible to obtainan analytical solution of the life cycle of SARS-CoV-2 based on a deterministic model. To do this, this work solved a system of twelve differential equations where we obtained two points of equilibrium. The first critical point corresponds to the initial conditions regarding the virus entry into the cell without replication in the cell, and the second involved one is the process of the transcription and replication of the virus in the infected cell.
Keywords: SARS-CoV-2; viral kinetics; mathematical modeling